Synergistic electrodeposition of bilayer films and analysis by Raman spectroscopy - Elmasly, Saadeldin E. T.; Guerrini, Luca; Cameron, Joseph; Kanibolotsky, Alexander L.; Findlay, Neil J.; Faulds, Karen; Skabara, Peter J. (Beilstein Journal of Organic Chemistry, 2018)
A novel methodology towards fabrication of multilayer organic devices, employing electrochemical polymer growth to form PEDOT and PEDTT layers, is successfully demonstrated. Moreover, careful control of the electrochemical conditions allows the degree of doping to be effectively altered for one of the polymer layers. Raman spectroscopy confirmed the formation and doped states of the PEDOT/PEDTT bilayer. The electrochemical deposition of a bilayer containing a de-doped PEDTT layer on top of doped PEDOT is analogous to a solution-processed organic semiconductor layer deposited on top of a PEDOT:PSS layer without the acidic PSS polymer. However, the poor solubility of electrochemically deposited PEDTT (or other electropolymerised potential candidates) raises the possibility of depositing a subsequent layer via solution-processing.
Keywords: bilayer; electropolymerisation; PEDOT; PEDTT; Raman

(untitled) - Menard, E.; Meitl, M. A.; Sun, Y.; Park, J.-U.; Shir, D. J.-L.; Nam, Y.-S.; Jeon, S.; Rogers, J. A. (Chem. Rev., 2007)

(untitled) - Teichler, A.; Perelaer, J.; Schubert, U. S. (J. Mater. Chem. C, 2013)

(untitled) - Huang, J.-H.; Ho, Z.-Y.; Kuo, T.-H.; Kekuda, D.; Chu, C.-W.; Ho, K.-C. (J. Mater. Chem., 2009)

(untitled) - Duan, L.; Hou, L.; Lee, T.-W.; Qiao, J.; Zhang, D.; Dong, G.; Wang, L.; Qiu, Y. (J. Mater. Chem., 2010)

(untitled) - Lee, J.-K.; Chatzichristidi, M.; Zakhidov, A. A.; Taylor, P. G.; DeFranco, J. A.; Hwang, H. S.; Fong, H. H.; Holmes, A. B.; Malliaras, G. G.; Ober, C. K. (J. Am. Chem. Soc., 2008)

(untitled) - Zakhidov, A. A.; Lee, J.-K.; Fong, H. H.; DeFranco, J. A.; Chatzichristidi, M.; Taylor, P. G.; Ober, C. K.; Malliaras, G. G. (Adv. Mater., 2008)

(untitled) - Estrany, F.; Aradilla, D.; Oliver, R.; Alemán, C. (Eur. Polym. J., 2007)

(untitled) - Estrany, F.; Aradilla, D.; Oliver, R.; Armelin, E.; Alemán, C. (Eur. Polym. J., 2008)

(untitled) - Aradilla, D.; Estrany, F.; Alemán, C. (J. Phys. Chem. C, 2011)

(untitled) - Goldoni, F.; Langeveld-Voss, B. M. W.; Meijer, E. W. (Synth. Commun., 1998)

(untitled) - Spencer, H. J.; Skabara, P. J.; Giles, M.; McCulloch, I.; Coles, S. J.; Hursthouse, M. B. (J. Mater. Chem., 2005)

(untitled) - Garreau, S.; Louarn, G.; Buisson, J. P.; Froyer, G.; Lefrant, S. (Macromolecules, 1999)

(untitled) - Tran-Van, F.; Garreau, S.; Louarn, G.; Froyer, G.; Chevrot, C. (J. Mater. Chem., 2001)

(untitled) - Garreau, S.; Louarn, G.; Froyer, G.; Lapkowski, M.; Chauvet, O. (Electrochim. Acta, 2001)

(untitled) - Kalbáč, M.; Kavan, L.; Dunsch, L. (Synth. Met., 2009)

(untitled) - Kocharova, N.; Lukkari, J.; Viinikanoja, A.; Ääritalo, T.; Kankare, J. (J. Phys. Chem. B, 2002)

(untitled) - Everall, N. J. (Analyst, 2010)

(untitled) - de Jong, M. P.; van IJzendoorn, L. J.; de Voigt, M. J. A. (Appl. Phys. Lett., 2000)